Welfare Effects of Adverse Weather through Speed Changes in Car Commuting Trips - Muhammad Sabir; Jos van Ommeren; Mark Koetse; Piet Rietveld (Tinbergen Institute, 2008)
This paper investigates the welfare effect of adverse weather through changes in the speed of individuals' car commuting trips in the entire Netherlands. Weather measurements are local and time specific (hourly basis). As most commuters travel twice a day between home and work, we are able to estimate the effect of adverse weather employing panel data techniques, which is novel in this context. We find that for most commuters the welfare effects of adverse weather conditions are negative but small. However, the commuters' welfare costs due to rain are rather substantial during rush hours in congested areas (and up to 15 percent of the overall commuting costs).
Keywords: R41; 330; adverse weather speed; Wetter; Reisekosten; Kraftfahrzeug; Wohlfahrtsanalyse; Niederlande; Pendelverkehr